Experimental analysis on energy recovery ventilator with latent heat exchanger using hollow fiber membrane. (15th February 2023) - Cho, Hye-Jin; Cheon, Seong-Yong; Jeong, Jae-Weon
Highlights: A prototype of hollow fiber membrane-based energy recovery ventilation unit was developed. Seasonal operation sequences of the proposed system were established. Sensible effectiveness: 53.6–80.1%, latent effectiveness: 68.1–73.1%, enthalpy effectiveness: 76.1–89.6% Operating performance and energy efficiency satisfied minimum requirements from the local test standard. Proposed system could have a 16.8–29.8% higher ventilation load reduction potential than existing ERVs. Abstract: A novel energy recovery ventilation unit with a hollow fiber membrane-based latent heat exchanger is proposed and built to experimentally evaluate its operational performance and energy efficiency. The proposed system consists of a latent heat exchanger fabricated by hollow fiber membrane to accommodate the latent load of introduced outdoor air and a flat-plate sensible heat exchanger to eliminate the sensible load. Annual operating strategies are established based on outdoor air conditions, and experiments are conducted under each operation mode. Further, the thermal behaviors of air (including temperature and humidity) under each operation mode are described according to the measured data. The proposed system exhibits a sensible, latent, and enthalpy effectiveness of 53.6–80.1%, 68.1–73.1%, and 76.1–89.6%, respectively. As for the energy efficiency of the proposed ventilation unit, the coefficients of energy are 29.63 and 15.29 under the summer and winter operation modes, respectively, which meet the minimum energy performance requirements of the local test standard. Finally, the potential reduction in the ventilation load for each operation mode is estimated using the measured data. The proposed unit could reduce the ventilation load by 75.4%and 77.3% in summer and winter operation modes, respectively. These results reveal that the proposed ventilation unit demonstrates significant application potential in improving the operating and energy performance of buildings.